Students' entrepreneurial self-efficacy: does the teaching method matter?. Issue 8 (9th November 2015) - Abaho, Ernest; Olomi, Donath R.; Urassa, Goodluck Charles
Abstract : Purpose: – The purpose of this paper is to examine the various entrepreneurship teaching methods in Uganda and how these methods relate to entrepreneurial self-efficacy (ESE). Design/methodology/approach: – A sample of 522 final year students from selected universities and study programs was surveyed using self-reported questionnaires. Findings: – There was a statistically significant positive relationship between ESE and lecturers' business experience. Interacting with successful people, personal reading and handout notes, class presentations and imaginary case studies had a statistically significant positive relationship with ESE. There was no statistical significance in the relationship between ESE and some teaching methods. A positively significant correlation was also observed between lectures' business experience and the choice of teaching method(s). Research limitations/implications: – Further research should explore how various methods are used to teach different aspects of entrepreneurship as well as the attitudes and perceptions of entrepreneurship educators about entrepreneurial experience and its relevancy in entrepreneurship education. Practical implications: – Lecturers should seek opportunities for attaining business experience through practice and business networks. Institutions should orient lecturers through different teaching styles and train them on how to relate learning outcomes to learning environments as well as investing in learning aids. Originality/value: – The study provides insights about the most feasible methods of activating ESE in the most practical and efficient ways. It also informs readers about the state of learning technologies from a developing country's perspective.